PCB2 improves porcine oocyte maturation by enhancing TZP-mediated cumulus-oocyte communication - Yuwen Luo; Qingrui Zhuan; Dan Zhou; Hongyu Liu; Jun Li; Xiangwei Fu (Theriogenology, 2026)

A mechanically stable and kinetically optimized organic-inorganic hybrid SEI for ultra-long lifespan zinc metal anodes - Chenyi Cao; Dan Lu; Chao Li; Xin Tan; Tianci Li; Shoubin Zhou; Xueping Tang; Sean C. Smith; Zhao Fu; Hongjia Song; Yunya Liu; Xiangli Zhong; et al. (Chemical Engineering Journal, 2026)

From agronomic performance to behavioral adoption of biochar‑based slow‑release fertilizer in saline‑alkali rice: A single‑season field trial and survey‑based SEM analysis - Zhixia Wang; Chang Dong; Junqiang Dong; Yang Cheng; Yuan Hu; Dan Liu; Yan Zhang; Zhen Qiu; Yanjiang Cai; Yongfu Li; Cheng Fu; Bing Yu (Journal of Environmental Chemical Engineering, 2026)

Metal Bi-coupled chiral nanoscale structures enhance spin-polarized electrons to promote photocatalytic CO2 reduction - Dan Wu; Yanni Lang; Liang Xu; Qiyuexin Wang; Qiu Fu; Bingli Li; Xinye Zhao; Zhaoyi Yin; Yongjin Li; Dacheng Zhou; Yangke Cun; Zhiguo Song; et al. (Chemical Engineering Journal, 2026)

Enzymatic Preparation of Ejiao (Colla Corii Asini) Peptides and Their Preliminary Mechanism of Melanogenesis Inhibition - Xichao Fu; Shangwei Guo; Meijin Li; Zhijie Chen; Dan Liu; Cuicui Men; Na Yang; Xiaobo Duan; Xiaolu Tang; Yaru Zhang; Haibin Liu; Minghao Liu; et al. (International Journal of Peptide Research and Therapeutics, 2026)

CIDA: A context-informed decoupling approach for soil trace element estimation using spaceborne cross-sensor data - Yishan Sun; Dan Li; Hao Jiang; Kai Jia; Shuisen Chen; Chongyang Wang; Xingda Chen; Jing Zhang; Jinyue Chen; Xiao Zhang; Wenlin Fu; Weibin Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Bi-doped SnO2 porous nanospheres for trace formaldehyde sensing at room temperature - Dan Meng; Yihang Fu; Lijun Li; Lei Zhang; Zongsheng Xie; Jian Qi; Xiaoguang San (Chemical Engineering Journal, 2026)

Synergistic SHH activation and BMP inhibition remodel progenitor niche for enhanced hair cell generation - Chunying Li; Dan He; Wenxu Tang; Liping Fu; Xilin Tan; Yao Yao; Xiaolei Yin (Science China Life Sciences, 2026)

Biocontrol mechanism of Streptomyces sp. MEPF0303 against Sclerotium delphinii causing Dendrobium officinale southern blight revealed by multi-omics analysis - Qiao Liu; Yu-Jie Chen; Jing Shi; Yong-Jing Zhang; Hai-Lan Fu; Zi-Ling Tao; Tao Zhou; Zhi-wu Tan; Ji-Luan Zhang; Ji-Hong Jiang; Lu-Dan Li (Pesticide Biochemistry and Physiology, 2026)

Ocean acidification exacerbates UVR-induced inhibition of photosystem II and I in Corallina officinalis - Di Zhang; Zhengke Shen; Dan Hu; Jiazhen Sun; Futian Li; Li Gao; Feng Fu; Tao Jiang (Journal of Photochemistry and Photobiology B: Biology, 2026)

A specific strategy for accelerating strength-development rate of self-generated proppants: the gel effect related autoacceleration - Xianyan Ren; Zhenyong Li; Yating Chen; Xiaoji Fu; Yirui Zhang; Dan Fang; Xirui Chen; Cheng Bian (Fuel, 2026)

Environmentally relevant doses of fluoride exposure mediate kidney injury by affecting Tregs/Teffs homeostasis - Bingshu Liu; Siqi Zhu; Dan Wei; Qiong Zhang; Guiyu Fu; Xiudian Li; Yanhui Gao; Wei Wei (Chemico-Biological Interactions, 2026)

Analysis of meteorological causes for a spring PM10 pollution episode over Hainan Island, China - Chuan-bo Fu; Li Dan; Jia-xiang Tang; Jin-he Tong (Atmospheric Research, 2026)

Hyperspectral phenotyping and GWAS identify novel QTLs for soybean photosynthetic rate - Li Wang; Ning Fu; Jinyu Zhang; Ao Shen; Yuanmeng Yu; Yanhong Wang; Xiaoli Guan; Dan Zhang; Fang Huang; Xiaoyong Yang; Deyue Yu; Zhongwen Huang; et al. (Theoretical and Applied Genetics, 2026)

Decoupling of Fe isotope and Fe3+/ΣFe in arc igneous rocks: Implications for crustal metasomatism and its contribution to mantle redox - Li-Tao Ma; Li-Qun Dai; Zi-Wei Yao; Zi-Fu Zhao; Ye-Dan Hu; Zhen-Wu Chen; Guo-Chao Sun (Geochimica et Cosmochimica Acta, 2026)

A new sesquiterpene and other constituents from Dendrobium nobile Lindl. and their chemotaxonomic significance - Wenyuan Zhou; Yi Yang; Xiaonan Li; Xiujuan Fu; Siwei Chen; Hui Lei; Ying Zhang; Dan Zhang; Chunlian Wu (Biochemical Systematics and Ecology, 2026)

Decoding gibberellin–strigolactone interaction networks in cereal crops toward a next-generation Green Revolution - Jie Hu; Yunzhe Wu; Shuang Zhang; Qiaoling Zhang; Zhe Chai; Dan Li; Danlin Zhao; Binghui Wu; Xiuhua Gao; Xueying Liu; Kun Wu; Xiangdong Fu (Molecular Plant, 2026)

First investigation into occurrence, trophodynamics, and risk implication of polychlorinated naphthalenes and polychlorinated biphenyls in a terrestrial food chain from Tibetan Plateau - Siyuan Xiong; Wenxiao Pan; Duo Bu; Kai Huang; Boyuan Hu; Shuyi Shen; Qiangying Zhang; Zeng Dan; Xiaomei Cui; Yingming Li; Guorui Liu; Qinghua Zhang; et al. (Environmental Pollution, 2026)

Three-phase interface modulation strategy for SERS detection of pathogenic bacteria in complexed media - Sensen Zhou; Ruiqi Peng; Boyan Zhao; Yong Wang; Chen Fu; Wei Deng; Dan Li (Chemical Engineering Journal, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Effect of the combination of lactic acid, ε-poly-L-lysine and sodium isoascorbate on the swelling, microbiomics variation, and quality attributes of vacuum-packed fresh cut lotus root - Jiahui Jiang; Qianlong Shi; Dan Li; Qingmin Chen; Cong Han; Jing Wei; Maorun Fu; Huaimei Cao; Xiaofei Xin (Postharvest Biology and Technology, 2026)

Genetic diversity of Theileria species identified from questing and parasitic ticks in selected areas in Qinghai, China - Yuan Han; Zhi Li; Yong Fu; Junlong Liu; Dan Jia; Chunhua Li; Hong Yin; Mengtong Lei (Veterinary Research Communications, 2026)

Effects of Lactobacillus Acidophilus Mediated Improvement of Intestinal Barrier in Mice with Autism - Yong Song; Jia Shi; XiaoYi Fu; Dan Fu; Li Xu; WeiMei Liu; JingJing Cao; YaoCheng Ding; ShuPeng Huang; Lin Zhou; Kai Qian (Probiotics and Antimicrobial Proteins, 2026)

Solar-driven catalytic platforms for closed-loop carbon cycling: CO2 assisting biomass conversion - Jingwen Jiang; Yiheng Wang; Yuanjie Li; Junxi Huang; Weiping Zhang; Dan Wang; Dong Xu; Dong Fu; Pan Zhang; Lemeng Wang; Kun Zhao (Bioresource Technology, 2026)

Biodegradable microplastics exert differential impacts from polyethylene on pesticide fate in soil-earthworm systems: insights into degradation selectivity and microbial mechanisms - Dan Yang; Ruiting Dong; Furong Fu; Lixia Zhao; Xiaojing Li; Huike Ye; Mohan Bai; Yang Sun (Environmental Pollution, 2026)

Preparing both mechanically robust and highly conductive semi-solid supercapacitor using environment-friendly gelatin-based hydrogel with cellulose fibers and ionic liquid - Yunxia Yang; Dan Li; Ningguo Yang; Tengfei Yan; Yangbing Wen; Ning Yan; Fu Guo (Chemical Engineering Journal, 2025)

Late Cenozoic Climates and Mountains Drove Diversification of the Pardosa laura Species Complex From Eastern China - Li‐Juan Liu; Dan Fu; Shu‐Qiang Li; Yu‐Fa Luo (Journal of Biogeography, 2025)
Aim To test how evolutionary processes of spiders in mountain ranges of eastern China were in response to environmental changes, we analyze the correlation between diversification of the Pardosa laura species complex (Araneae, Lycosidae) and historical climates and mountains in this region. Methods We reconstruct phylogenetic relationships and patterns of phylogeography and genetic diversity using mtDNA data from samples spanning the full range of the species complex P. laura in eastern China. Results The P. laura species complex clustered into four lineages: Lineage I includes five haplotypes from the areas to the north of the Yinshan‐Yanshan Mountains; Lineage II consists of 23 haplotypes from the areas between the Qinling Mountains–Huaihe River Line and the Nanling Mountains; Lineage III and IV are composed of 21 and 62 haplotypes, respectively, from the areas between the Yinshan‐Yanshan Mountains and the Nanling Mountains. Each lineage corresponds to that, grouped from haplotype network analyses, with the same geographic distribution areas. All four lineages initially diversified during about 1.43 and 0.24 Ma ago (Ma) in relation to the Pleistocene glacial‐inglacial cycles. The biogeographic reconstructions suggest that the species complex P. laura most likely originated in central China around 7.68 (11.17–4.85) Ma in relation to the recent ( approximately 8 Ma) expansion of grasslands and retraction of forests. The inter‐colony dispersal between central China and northeastern China occurred during the late Neogene, between around 7.68 and 3.14 Ma. Central China is an important dispersal center, with dispersal to southwestern and northern China between the late Pliocene and middle Pleistocene, approximately 3.14–2.89 and 2.89–1.43 Ma, respectively. Main Conclusions The contemporary genetic structure of the P. laura species complex presents a high correlation between lineages and geographic distribution. The historical phylogeographic patterns suggested that the late Cenozoic climate changes and the mountainous corridors and isolation events, as well as the lineage dispersals and ecological adaptations shaped the diversification of a spider species complex in eastern China over long timescales.

Electrocatalytic oxidation of ranitidine using a fluorinated blue titanium dioxide nanotube array electrode - Jianhui Xu; Zhijie Cui; Xin Fu; Dan Li; Yanyan Zeng; Yunfei Zhang; Peng Liu; Xiangteng Mo; Kexin Cao; Zijie Shen; Shangkun Ye (Journal of Environmental Chemical Engineering, 2025)

Influential mechanisms of light exposure on the reduction of V5+ by extracellular polymeric substances: Role of the reductive and nonreductive components - Wen Qing; Dan Zhou; Liyuan Fu; Tianxin Zhou; Haoran Xiong; Mengmeng Liang; Yi Huang; Jinshu Zhang; Yubin Li; Chengye Yang; Jingxian Qi (Journal of Environmental Chemical Engineering, 2025)

Impact of landscape configuration on water purification capacity: A case study in a plateau lakeside wetland - Jie Li; Dan Li; Yu Fu; Yu Huang; Xiaoyan Li; Binghui Zheng (Ecological Engineering, 2025)

Synergistic catalysis of CuxFey/CeO2 bimetallic catalysts for oxidative dehydrogenation of C2H6 with CO2 - Dan Guo; Zouxuan Qi; Zelong Fu; Zhenli Lv; Li Kang; Feigang Zhao; Tongrui Wan; Shengping Wang; Xinbin Ma (Chemical Engineering Journal, 2025)

Configuration-locked near-planar D-A-D polymers for ultrahigh stability electrochromic supercapacitors - Haichang Fu; Hongtao Fang; Junze Jin; Yicai Lu; Weijun Li; Qidi Huang; Yanxian Jin; Zhangxin Chen; Dan Chen; Kai Huang (Chemical Engineering Journal, 2025)

Molecular evolution of the bZIP family in allotetraploid Gossypium and GhbZIP017 function under drought stress - Fangting Ye; Jing He; Zhaowei Li; Huanyu Wu; Ziyou Zhang; Dan Fu; Yanchun Li; Jinwen Huang; Changlan Zhu; Kai Fan (Plant Cell Reports, 2025)

Multiomics approach towards the detoxification of cadmium in Fritillaria cirrhosa using citrulline and zinc oxide nanoparticles in Qinghai-Tibet’s ecosystems - Jialu Wang; Zemin Yang; Dan Gao; Haitao Liu; Haobo Zhang; Huigan Xie; Shaobing Fu; Xiwen Li (Journal of Hazardous Materials, 2025)

The influential mechanisms of solution chemistry on the stability and transport of vanadium-titanium magnetite tailing colloids - Qidi Zhao; Dan Zhou; Haoran Xiong; Liyuan Fu; Tianxin Zhou; Jianing Sun; Mingzheng Huang; Jinshu Zhang; Yubin Li; Chengye Yang; Yi Huang (Journal of Hazardous Materials, 2025)

Transcriptomics revealed the regulatory mechanism of phenylalanine butyramide on the growth and biofilm formation of Lactobacillus paracasei - Xinyu Fan; Yize Li; Yin Fu; Pengcheng Chen; Dan Wu; Pu Zheng (Food Bioscience, 2025)

Assessment of abuse potential of furanylfentanyl and tetrahydrofuranylfentanyl - Yuanyuan Chen; Miaojun Lai; Xiangyu Li; Yanling Qiao; Deli Xu; Dan Fu; Bin Di; Peng Xu (Psychopharmacology, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

A hydrophobic cathode design towards high-stability Zn-air batteries: Coupling FeTAP molecules with self-supporting edge-rich graphene membrane - Jiachen Meng; Yulei Zhang; Xuemin Yin; Yanqin Fu; Dan Wen; Qiang Song; Hejun Li (Chemical Engineering Journal, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Preparation of hydrophilic and antibacterial nanofiltration membrane by post-grafting N-(3-Aminopropyl)-imidazole - Yu Fu; Fangbo Zhao; Yingzheng Liu; Ruiqi Li; Hongxu Chen; Liu Yang; Zhiguo Li; Mingcong Wu; Dan Wang (Journal of Environmental Chemical Engineering, 2025)

Lightweight deep learning model for embedded systems efficiently predicts oil and protein content in rapeseed - Mengshuai Guo; Huifang Ma; Xin Lv; Dan Wang; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Organic photothermal cocrystal directs Janus solar steam evaporator for efficient and scalable seawater desalination - Shouzhen Li; Chenfei Yang; Yi Su; Mengran Liu; Siyao Fu; Guangyao Zhao; Dan He; Lingjie Sun; Xiaotao Zhang; Wenping Hu (Chemical Engineering Journal, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

Chemistry for water treatment under nanoconfinement - Wanyi Fu; Ziyao Liu; Dan Li; Bingcai Pan (Water Research, 2025)

Effectiveness and mechanism of using sodium alginate-magnesium silicate carrier in UASB reactor to resist shock loading of coking wastewater - Yi Jiang; Wenlai Xu; Yizhi Zhang; Ruoxi Yan; Yifei Xie; Dan Zhang; FengLin Jia; Linshan Yang; Shah Zaib; Ruiyang Li; Pan Li; Songyu Fu; et al. (Journal of Cleaner Production, 2025)

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Soil and litter microbiomes as joint drivers of ecosystem multifunctionality in a 60-year-old forest plantation - Shu-Yi-Dan Zhou; Xu Li; Josep Peñuelas; David T. Tissue; Roy Neilson; Xujun Liu; Zhiyang Lie; Fu-Yi Huang; Junhua Yan; Dong Zhu; Juxiu Liu (Journal of Environmental Management, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Changes in Type 1 Diabetes-Associated Gut Microbiota Aggravate Brain Ischemia Injury by Affecting Microglial Polarization Via the Butyrate–MyD88 Pathway in Mice - Xianzhang Zeng; Can Ma; Wenchao Fu; Yongmei Xu; Rui Wang; Dan Liu; Lijuan Zhang; Narisu Hu; Dongmei Li; Wenzhi Li (Molecular Neurobiology, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Origin of the coeval Nb-enriched and arc mafic igneous rocks: Implications for Paleozoic tectonic evolution of the Southwestern Tianshan - Li-Tao Ma; Li-Qun Dai; Ye-Dan Hu; Zi-Fu Zhao (Chemical Geology, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Comprehensive physicochemical indicators analysis and quality evaluation model construction for the post-harvest ripening rapeseeds - Qiuhui Xu; Jie Wang; Dan Wang; Xin Lv; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Metabolomics integrated with mass spectrometry imaging reveals novel action of tetramethylpyrazine in migraine - Ziwei Xing; Yu Chen; Junren Chen; Cheng Peng; Fu Peng; Dan Li (Food Chemistry, 2024)

Exposure to toluene diisocyanate induces dysbiosis of gut-lung homeostasis: Involvement of gut microbiota - Yuxuan Gou; Fu Lin; Li Dan; Dianyu Zhang (Environmental Pollution, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Shallow groundwater table fluctuations weaken nitrogen accumulation in the thin layer vadose zone of cropland around plateau lakes, Southwest China - Qingfei Chen; Anqiang Chen; Jinheng Min; Lin Li; Wanli Hu; Chi Wang; Bin Fu; Shufang Guo; Dan Zhang (Science of The Total Environment, 2024)

Corrigendum to “Spatial heterogeneity of ecosystem service bundles and the driving factors in the Beijing-Tianjin-Hebei region” [J. Clean. Prod. 479 (2024) 144006] - Qing Li; Dan Li; Jinfeng Wang; Sheng Wang; Rende Wang; Gang Fu; Yixiao Yuan; Zhenhua Zheng (Journal of Cleaner Production, 2024)

Spatial heterogeneity of ecosystem service bundles and the driving factors in the Beijing-Tianjin-Hebei region - Qing Li; Dan Li; Jinfeng Wang; Sheng Wang; Rende Wang; Gang Fu; Yixiao Yuan; Zhenhua Zheng (Journal of Cleaner Production, 2024)

Valence electronic engineering of hollow-nanocube-structured CoFeNi-layered double hydroxides for highly efficient oxygen evolution - Lu Liu; Lingxing Zan; Yunchuan Tu; Hongling Zhang; Dan Zhu; Zhe Li; Jiawen Zheng; Zhuangzhuang Zhang; Yu Sun; Qiang Weng; Jian Li; Qingbo Wei; et al. (Chemical Engineering Journal, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Two-way coupling fluid–structure interaction analysis on dynamic response of offshore wind turbine - Fen Li; Jiaojiao Fu; Jiahui Chen; Dan Hu (Marine Georesources & Geotechnology, 2024)

Hohaiivirga grylli gen. nov., sp. nov., a New Member of the Family Methylobacteriaceae, Isolated from Cricket (Gryllus chinensis) - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wei He; Lu Wang; Zi-Yue Fu; Wen-Jun Li; Ai Hua Zhang; Dao-Feng Zhang (Current Microbiology, 2024)

Spatiotemporal analysis of microstructure, sensory attributes, and full-spectrum metabolomes reveals the relationship between bitterness and nootkatone in Alpinia oxyphylla miquel fruit peel and seeds - Xiaolu Chen; Yong Yang; Maoyuan Wang; Qin Tian; Qian Jiang; Xuan Hu; Weiguo Ye; Wanyun Shen; Xueting Luo; Xueyan Chen; Chao Yuan; Dan Wang; et al. (Food Research International, 2024)

Transcriptomics to evaluate the influence mechanisms of ethanol on the ester production of Wickerhamomyces anomalus with the induction of lactic acid - Wenqin Cai; Yin Wan; Yanru Chen; Haowei Fan; Mengxiang Li; Shengwen Wu; Pei Lin; Tingting Zeng; Huibo Luo; Dan Huang; Guiming Fu (Food Microbiology, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

A new 3D printing strategy by enhancing shear-induced alignment of gelled nanomaterial inks resulting in stronger and ductile cellulose films - Yunxia Yang; Dan Li; Ning Yan; Fu Guo (Carbohydrate Polymers, 2024)

Secular mantle wedge evolution due to variable slab fluid metasomatism: Evidence from Permian-Triassic mafic igneous rocks in the Paleo-Tethys tectonic regime - Ye-Dan Hu; Li-Qun Dai; Li-Tao Ma; Zi-Fu Zhao (Chemical Geology, 2024)

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Shallow groundwater table fluctuations promote the accumulation and loss of phosphorus from surface soil to deeper soil in croplands around plateau lakes in Southwest China - Qingfei Chen; Wenchao Li; Anqiang Chen; Jinheng Min; Wanli Hu; Chi Wang; Bin Fu; Dan Zhang (Journal of Environmental Management, 2024)

Impact of thermal ultrasound on enzyme inactivation and flavor improvement of sea cucumber hydrolysates - Yi-chao Cheng; Dan-li Jin; Wen-tao Yu; Bo-yang Tan; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2024)

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Determination of chloropropanol esters and glycidyl esters in nutritional foods by gas chromatography–tandem mass spectrometry based on acid hydrolysis and solid-phase extraction - Yi Li; Dan Chen; Wusheng Fu; Yan Yang; Huafeng Chen; Lei Ni; Hongjing Chen; Dingguo Jiang; Sophia Zhang; Rongjuan Gui (Food Additives & Contaminants: Part A, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

High mineralization efficiency of chlorobenzene oxidation using a metal-interaction strengthening MnCoOx catalyst derived from ZIF-67 - Shuangshuang Fu; Dongjie Yan; Dan Tao; Ning Yang; Kaixian Liu; Yifan Rong; Lu Li; Chi He (Fuel, 2024)

Addressing redox shuttling in Li-O2 batteries: Mechanistic insights by synchrotron X–ray tomography - Dan Li; Fu Sun; Yuqing Zhang; Yulong Liu; Hao Sun; Haiming Xie; Jia Liu; Seung-Taek Myung; Jiefang Zhu (Chemical Engineering Journal, 2024)

Transcriptomic profiling reveals color variation mechanism of Fritillaria cirrhosa for the molecular plant breeding - Ye Wang; Zemin Yang; Xinyue Wang; Ziyi Liu; Huigan Xie; Shaobing Fu; Dan Gao; Xiwen Li (Acta Physiologiae Plantarum, 2024)

Novel material to enhance the integrity of CCUS cement sheath: Exploration and application of calcium aluminate cement - Peng Gong; Huacai Fu; Dan He; Yuanpeng Wu; Kaiyuan Mei; Chunmei Zhang; Xin He; Tao Liu; Shangdong Li; Xiaowei Cheng (Gas Science and Engineering, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Propyl gallate exposure affects the mouse 2-cell stage embryonic development through inducing oxidative stress and autophagy - Sheng-Ji Yang; Fu-Yi Yang; Yi-Nuo Zou; Yong-Sheng Wang; Zhi-Ming Ding; Li-Dan Zhang; Xu Zhou; Ming Liu; Ze-Qun Duan; Li-Jun Huo (Food and Chemical Toxicology, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Dispersion of sandy sediments during marine–continental transition: An integrated study from the Late Paleozoic western Ordos Basin - Zhiwei Wang; Lei Liu; Jianling Hu; Feng Wang; Dan Li; Jingqi Zhang; Shuyue Zhu; Rui Zhang; Fei Zhao; Chenggong Zhang; Siyi Fu; Hongde Chen (Marine and Petroleum Geology, 2024)

Long-term seawall barriers lead to the formation of an urban coastal lagoon with increased antibiotic resistome - Shu-Yi-Dan Zhou; Kai Yang; Roy Neilson; Hu Li; Hong-Zhe Li; Yan-Yan Zhou; Juxiu Liu; Jian-Qiang Su; Fu-Yi Huang (Journal of Environmental Management, 2024)

Corrigendum to “Procyanidin B2: A promising multi-functional food-derived pigment for human diseases” [Food Chem. 420 (2023) 136101] - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Fluctuating redox conditions accelerate the electron storage and transfer in magnetite and production of dark hydroxyl radicals - Dan Li; Jieyi Sun; Yibo Fu; Wentao Hong; Heli Wang; Qian Yang; Junhong Wu; Sen Yang; Jianhui Xu; Yunfei Zhang; Yirong Deng; Yin Zhong; et al. (Water Research, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

The characteristic of compound drought and saltwater intrusion events in the several major river estuaries worldwide - Dan Li; Bingjun Liu; Yang Lu; Jianyu Fu (Journal of Environmental Management, 2024)

Development of MoS2-stainless steel catalyst by 3D printing for efficient destruction of organics via peroxymonosulfate activation - Yufeng Liu; Jianhui Xu; Xin Fu; Pengxu Wang; Dan Li; Yunfei Zhang; Shenggui Chen; Chunhui Zhang; Peng Liu (Journal of Environmental Sciences, 2024)

Combined pollution and soil microbial effect of pesticides and microplastics in greenhouse soil of suburban Tianjin, Northern China - Furong Fu; Yang Sun; Dan Yang; Lixia Zhao; Xiaojing Li; Liping Weng; Yongtao Li (Environmental Pollution, 2024)

Surimi freshness monitoring of 4D printing material with anthocyanin - Jun-qi Zhan; Jing-jing Fu; Dan-li Jin; Yan-wei Yuan; Shi-ke Shen; Gao-shang Li; Yue-wen Chen (Journal of Food Engineering, 2023)

Improving the flavor of tilapia fish head soup by adding lipid oxidation products and cysteine - Huixian Fu; Qiaohui Feng; Dan Qiu; Xuanri Shen; Chuan Li; Yanfu He; Wenting Shang (Food Chemistry, 2023)

Simulation of runoff process based on the 3-D river network - Yuan Xue; Chao Qin; Baosheng Wu; Ga Zhang; Xudong Fu; Hongbo Ma; Dan Li; Bingjie Wang (Journal of Hydrology, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

The strength characteristics and competitive failure mechanism of primary coal-rock combination considering interface damage quantity - Kai Wang; Qiang Fu; Chao Xu; Zibo Ai; Dan Li; Longyong Shu (Fuel, 2023)

Revealing the chemical differences and their application in the storage year prediction of Qingzhuan tea by SWATH-MS based metabolomics analysis - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Dan Zou; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Research International, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Coloration of cotton fibers with inorganic pigments using a transient high-temperature technology - Qimeng Zhu; Zhuan Fu; Liangjun Xia; Xiaofeng Wang; Zhaozixuan Zhou; Dan Sheng; Xinjie Wei; Junyao Gong; Sijie Zhou; Wenbin Li; Chunhua Zhang (Journal of Cleaner Production, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Two-point-one-line modularized strategy combined with Holliday-junction button probes for multiloci SNPs long-range distribution analysis - Wang Luo; You Wu; Xueping Chen; Li Zhang; Li Wang; Dan Bai; Qian Liu; Ting Wang; Hongyan Yu; Yaxing Xie; Yixin Fu; Zhongzhong Wang; et al. (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Procyanidin B2: A promising multi-functional food-derived pigment for human diseases - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2023)

3-D transient electromagnetic inversion based on explicit finite-difference forward modeling - Fei Li; Qiang Tan; Lai-Fu Wen; Dan Huang (Applied Geophysics, 2023)

Current advances in the anti-inflammatory effects and mechanisms of natural polysaccharides - Dan Yuan; Chao Li; Qiang Huang; Xiong Fu; Hao Dong (Critical Reviews in Food Science and Nutrition, 2023)

NIR responsive composite nanomaterials with in-situ deposition of cascaded nanozymes for multiple synergistic therapy of bacterial infection in diabetic mice - Yan Zhang; Chunping Wen; Yijun Liu; Anqi Li; Qiuyan Guo; Xuan Zhang; Li Fu; Shan Xu; Dan Qiao; Pengwu Zheng; Wufu Zhu; Qingshan Pan (Chemical Engineering Journal, 2023)

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Jing Zhang; Fu Xiao; Ao Li; Tianyou Ma; Kan Xu; Hanbei Zhang; Rui Yan; Xing Fang; Yuanyang Li; Dan Wang (Building and Environment, 2023)

Validation of the detected Dry–Wet Abrupt Alternation by developing a weighting analysis method - Jianyu Fu; Bingjun Liu; Yang Lu; Manlin Liang; Xuejin Tan; Dan Li; Zeqin Huang (International Journal of Climatology, 2023)
The phenomenon of sudden drought after pluvial (or heavy pluvial after drought) is known as the Dry–Wet Abrupt Alternation (DWAA). This kind of disaster has been evaluated globally based on various DWAA indices. However, few validations have been performed to compare the various DWAA indices. Given that directly validating the identified DWAA events remains difficult because of the limited historical records of DWAA events, in this study, we developed a simple weighting analysis method to cross‐validate the detected DWAA events using three widely‐used indices. The weighting analysis method can be used to estimate the effectiveness of the DWAA indices by calculating the ratio of the synchronous DWAA events (the DWAA events could be synchronously detected by different indices) to the total number of the detected DWAA events. Results suggest that the standard weighted average of precipitation (SWAP) index has better performance for detecting DWAA events in the Pearl River Basin (PRB) compared to other indices. The soil moisture synchronization, meteorological concentration and real DWAA records further testify that the SWAP is more capable of detecting the DWAA events in the PRB. Based on the validation, the SWAP‐derived DWAA events show that both dry–wet (D–W) events and wet–dry events are severe in the upstream sub‐basins in the PRB, while D–W events are more frequent in the downstream PRB. Our study provides a simple but effective method to validate the detected DWAA. The finding underscores the need to validate DWAA detection generated from multiple indicators before further research, and it could help develop adaptation strategies to improve resilience to combined extremes under changing climate.

Biomimetic optimized concept with Murray networks for accelerated solar-driven water evaporation - Ruofei Zhu; Ke Li; Dan Wang; Jipeng Fei; Jun Yan Tan; Shuzhou Li; Jichao Zhang; Hong Li; Shaohai Fu (Chemical Engineering Journal, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Long‐term variability in the fish assemblage around Japan over the last century and early warning signals of regime shifts - Yongjun Tian; Caihong Fu; Akihiko Yatsu; Yoshiro Watanabe; Yang Liu; Jianchao Li; Dan Liu; Yumeng Pang; Jiahua Cheng; Ching‐Hsein Ho; Shuyang Ma (Fish and Fisheries, 2023)
The marine ecosystems around Japan are very productive and have typical wasp‐waist structure dominated by small pelagic fishes such as sardine, exhibiting large low‐frequency fluctuations in biomass. Whereas studies on the variability in abundance of individual species such as sardine and anchovy are popular, only a few studies focused on the long‐term variability of fish assemblage around Japan. In this study, 13 species/taxa ranging from small forage to large predatory species and from warm‐ to cold‐water species were selected to indicate essential characteristics of the fish assemblage and their drivers were analysed based on fishery, oceanographic and climatic data sets from 1901 to 2018. Results show that two outstanding peaks during the 1930s and 1980s were characterized by abundant sardine. Additionally, species composition showed high similarities during similar temperature regimes while exhibiting contrasts during different temperature regimes. Variations and regime shifts in dominant patterns and fish community indices coincided well with the Atlantic Multidecadal Oscillation (AMO) and regional sea surface temperature (SST). Furthermore, gradient forest analysis identified AMO and regional SSTs as most important predictors of dominant patterns and fish community indices, suggesting that the decadal and multidecadal variability in the fish assemblage around Japan was forced by basin‐scale climate variability as inherent in the AMO through its connections with regional SSTs. Autocorrelation coefficient demonstrated that the ecological indicators have the potential to be early warning signals of regime shifts, which suggests the possibility of coming cold regime since around 2015 and has important implications for fisheries management.

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Evaluation of modified bitumen properties using waste plastic pyrolysis wax as warm mix additives - Chuanqiang Li; Haobo Wang; Chaoliang Fu; Shaosong Shi; Guannan Li; Qizheng Liu; Dan Zhou; Lin Jiang; Ying Cheng (Journal of Cleaner Production, 2023)

Electrochemical activation of peroxymonosulfate by 3D printed blue TiO2 nanotube arrays reactive electrochemical membrane for efficient degradation of acetaminophen - Jianhui Xu; Yufeng Liu; Dan Li; Chunhui Zhang; Xin Fu; Yunfei Zhang; Pengxu Wang; Jincheng Lu; Shenggui Chen; Lei Li (Journal of Environmental Chemical Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

CRISPR/Cas9-mediated targeted mutagenesis of two homoeoalleles in tobacco confers resistance to powdery mildew - Wang Xuebo; Li Dandan; Tan Xiaolei; Cai Changchun; Zhang Xinyao; Shen Zhan; Yang Aiguo; Fu Xiankui; Liu Dan (Euphytica, 2023)

Global ocean reanalysis CORA2 and its inter comparison with a set of other reanalysis products - Hongli Fu; Bo Dan; Zhigang Gao; Xinrong Wu; Guofang Chao; Lianxin Zhang; Yinquan Zhang; Kexiu Liu; Xiaoshuang Zhang; Wei Li (Frontiers in Marine Science, 2023)
We present the China Ocean ReAnalysis version 2 (CORA2) in this paper. We compare CORA2 with its predecessor, CORA1, and with other ocean reanalysis products created between 2004 and 2019 [GLORYS12v1 (Global Ocean reanalysis and Simulation), HYCOM (HYbrid Coordinate Ocean Model), GREP (Global ocean Reanalysis Ensemble Product), SODA3 (Simple Ocean Data Assimilation, version 3), and ECCO4 (Estimating the Circulation and Climate of the Ocean, version 4)], to demonstrate its improvements and reliability. In addition to providing tide and sea ice signals, the accuracy and eddy kinetic energy (EKE) of CORA2 are also improved owing to an enhanced resolution of 9 km and updated data assimilation scheme compared with CORA1. Error analysis shows that the root-mean-square error (RMSE) of CORA2 sea-surface temperature (SST) remains around 0.3°C, which is comparable to that of GREP and smaller than those of the other products studied. The subsurface temperature (salinity) RMSE of CORA2, at 0.87°C (0.15 psu), is comparable to that of SODA3, smaller than that of ECCO4, and larger than those of GLORYS12v1, HYCOM, and GREP. CORA2 and GLORYS12v1 can better represent sub-monthly-scale variations in subsurface temperature and salinity than the other products. Although the correlation coefficient of sea-level anomaly (SLA) in CORA2 does not exceed 0.8 in the whole region, as those of GREP and GLORYS12v1 do, it is more effective than ECCO4 and SODA3 in the Indian Ocean and Pacific Ocean. CORA2 can reproduce the variations in steric sea level and ocean heat content (OHC) on the multiple timescales as the other products. The linear trend of the steric sea level of CORA2 is closer to that of GREP than that of the other products, and the long-term warming trends of global OHC in the high-resolution CORA2 and GLORYS12v1 are greater than those in the low-resolution EN4 and GREP. Although CORA2 shows overall poorer performance in the Atlantic Ocean, it still achieves good results from 2009 onward. We plan to further improve CORA2 by assimilating the best available observation data using the incremental analysis update (IAU) procedure and improving the SLA assimilation method.

Effect of tea polyphenols on sturgeon myofibrillar protein structure in the in vitro anti-glycation model mediated by low temperature vacuum heating - Dan-li Jin; Jian-ling Wei; Fan-yu He; Ting-ting Chai; Shao-tian Ren; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2023)

Viscosity-triggered near-infrared fluorescence nanoprobe for in vivo non-invasive diagnosis of cancer - Wen-Juan Fu; Jian Ting Li; Wen Hui Qian; Xiang Ying Zhang; Dan Dan Ma; Yu Ting Wang; Qi Jia Zhang; Dong Zhu (Chemical Engineering Journal, 2023)

TMT-based quantitative proteomics analysis reveals the differential proteins between fresh and frozen-thawed sperm of yak (Bos grunniens) - Yilin Fan; Xiaowei Li; Yu Guo; Xiaoqiang He; Yanwen Wang; Dan Zhao; Yan Ma; Xinxin Feng; Jiyue Zhang; Jian Li; Xiangdong Zi; Xianrong Xiong; et al. (Theriogenology, 2023)

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Loss of SUN1 function in spermatocytes disrupts the attachment of telomeres to the nuclear envelope and contributes to non-obstructive azoospermia in humans - Qingxia Meng; Binbin Shao; Dan Zhao; Xu Fu; Jiaxiong Wang; Hong Li; Qiao Zhou; Tingting Gao (Human Genetics, 2023)

Analysis of coniferous tree growth gradients in relation to regional pollution and climate change in the Miyun Reservoir Basin, China - Li Fu; Yan Xu; Dan Zhao; Bingfang Wu; Zhihong Xu (Environmental Science and Pollution Research, 2023)
Forests play a crucial role in regulating regional climate and mitigating local air pollution, but little is known about their responding to such changes. This study aimed to examine the potential responses of Pinus tabuliformis , the major coniferous tree species in the Miyun Reservoir Basin (MRB), along an air pollution gradient in Beijing. Tree rings were collected along a transect, and ring width (basal area increment, BAI) and chemical characteristics were determined and related to long-term climatic and environmental records. The results showed that Pinus tabuliformis showed an overall increase in intrinsic water-use efficiency ( iWUE ) at all sites, but the relationships between iWUE and BAI differed among the sites. The contribution of atmospheric CO 2 concentration ( c a ) to tree growth was significant at the remote sites (> 90%). The study found that air pollution at these sites might have caused further stomatal closure, as evidenced by the higher δ 13 C levels (0.5 to 1‰ higher) during heavy pollution periods. The analysis of tree ring δ 15 N also revealed the potential of using δ 15 N to fingerprint major nitrogen (N) deposition, as shown in the increasing tree ring δ 15 N, and major nitrogen losses due to denitrification and leaching, as shown in the higher δ 15 N in tree rings during heavy rainfall events. Overall, the gradient analysis indicated the contributions of increasing c a , increasing water deficit and elevated air pollution to tree growth and forest development. The different BAI trajectories suggested that Pinus tabuliformis has the ability to adapt to the harsh environment in the MRB.

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Impacts of climate change on future hurricane induced rainfall and flooding in a coastal watershed: A case study on Hurricane Harvey - Xudong Li; Dan Fu; John Nielsen-Gammon; Sudershan Gangrade; Shih-Chieh Kao; Ping Chang; Mario Morales Hernández; Nathalie Voisin; Zhe Zhang; Huilin Gao (Journal of Hydrology, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Non-peer-reviewed data, effect measures, and meta-regression analysis on proton pump inhibitor use and COVID-19 - Dan-Na Wu; Li-Rong Jiao; Guo-Fu Li; Guo Yu (European Journal of Clinical Pharmacology, 2022)

Circular RNA circPBX3 promotes cisplatin resistance of ovarian cancer cells via interacting with IGF2BP2 to stabilize ATP7A mRNA expression - Lihua Fu; Dan Zhang; Nuo Yi; Yanjun Cao; Yaxian Wei; Wenjing Wang; Li Li (Human Cell, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Using data-limited approaches to assess data-rich Indian Ocean bigeye tuna: Data quantity evaluation and critical information for management implications - Ya’nan Li; Jiangfeng Zhu; Xiaojie Dai; Dan Fu; Yong Chen (Acta Oceanologica Sinica, 2022)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Critical transitions and ecological resilience of large marine ecosystems in the Northwestern Pacific in response to global warming - Shuyang Ma; Dan Liu; Yongjun Tian; Caihong Fu; Jianchao Li; Peilong Ju; Peng Sun; Zhenjiang Ye; Yang Liu; Yoshiro Watanabe (Global Change Biology, 2021)
Natural systems can undergo critical transitions, leading to substantial socioeconomic and ecological outcomes. “Ecological resilience” has been proposed to describe the capacity of natural systems to absorb external perturbation and reorganize while undergoing change so as to still retain essentially the same function, structure, identity, and feedbacks. However, the mere application of ecological resilience in theoretical research and the lack of quantitative approaches present considerable obstacles for predicting critical transitions and understanding their mechanisms. Large marine ecosystems (LMEs) in the Northwestern Pacific are characterized by great biodiversity and productivity, as well as remarkable warming in recent decades. However, no information is available on the critical transitions and ecological resilience of LMEs in response to warming. Therefore, we applied an integrated resilience assessment framework to fisheries catch data from seven LMEs covering a wide range of regions, from tropical to subarctic, in the Northwestern Pacific to identify critical transitions, assess ecological resilience, and reconstruct folded stability landscapes, with a specific focus on the effects of warming. The results provide evidence of the occurrence of critical transitions, with fold bifurcation and hysteresis in response to increasing sea surface temperatures (SSTs) in the seven LMEs. In addition, these LMEs show similarities and synchronies in structure variations and critical transitions forced by warming. Both dramatic increases in SST and small fluctuations at the corresponding thresholds may trigger critical transitions. Ecological resilience decreases when approaching the tipping points and is repainted as the LMEs shift to alternative stable states with different resilient dynamics. Folded stability landscapes indicate that the responses of LMEs to warming are discontinuous, which may be caused by the reorganization of LMEs as their sensitivity to warming changes. Our study clarifies the nonlinear responses of LMEs to anthropogenic warming and provides examples of quantifying ecological resilience in empirical systems at unprecedented spatial and temporal scales.

Effects of continuous cucumber cropping on crop quality and soil fungal community - Kaining Sun; Longyun Fu; Yang Song; Liang Yuan; Haoran Zhang; Dan Wen; Ning Yang; Xiao Wang; Yaoquan Yue; Xuhua Li; Kean Wang (Environmental Monitoring and Assessment, 2021)

Individual variation in metabolic rate, locomotion capacity and hypoxia tolerance and their relationships in juveniles of three freshwater fish species - Xu Pang; De-Yong Pu; Dan-Yang Xia; Xiao-Hong Liu; Shi-Hua Ding; Yun Li; Shi-Jian Fu (Journal of Comparative Physiology B, 2021)

Bridge Crack Semantic Segmentation Based on Improved Deeplabv3+ - Huixuan Fu; Dan Meng; Wenhui Li; Yuchao Wang (Journal of Marine Science and Engineering, 2021)
Cracks are the main goal of bridge maintenance and accurate detection of cracks will help ensure their safe use. Aiming at the problem that traditional image processing methods are difficult to accurately detect cracks, deep learning technology was introduced and a crack detection method based on an improved DeepLabv3+ semantic segmentation algorithm was proposed. In the network structure, the densely connected atrous spatial pyramid pooling module was introduced into the DeepLabv3+ network, which enabled the network to obtain denser pixel sampling, thus enhancing the ability of the network to extract detail features. While obtaining a larger receptive field, the number of network parameters was consistent with the original algorithm. The images of bridge cracks under different environmental conditions were collected, and then a concrete bridge crack segmentation data set was established, and the segmentation model was obtained through end-to-end training of the network. The experimental results showed that the improved DeepLabv3+ algorithm had higher crack segmentation accuracy than the original DeepLabv3+ algorithm, with an average intersection ratio reaching 82.37%, and the segmentation of crack details was more accurate, which proved the effectiveness of the proposed algorithm.

Long-Term Variability of Piscivorous Fish in China Seas Under Climate Change With Implication for Fisheries Management - Dan Liu; Yongjun Tian; Shuyang Ma; Jianchao Li; Peng Sun; Zhenjiang Ye; Caihong Fu; Kuowei Lan; Shijie Zhou (Frontiers in Marine Science, 2021)
Due to persistent fishing expansion in the China Seas over the past six decades, fisheries resources have been over-exploited; as a result, exploited fish have become smaller in size and younger in age. Marine piscivorous fish constituted a large portion of Chinese fisheries catch, long-term variability of which has rarely been investigated despite intense fishing pressure and climate change. In this study, we attempt to identify their responses to climate change and fishing activities and to provide scientific basis for sustainable exploitation of these resources. Seven taxa from pelagic to demersal species inhabiting either cold-water or warm-water were selected to represent the piscivorous fish assemblage in the China Seas. Total catch of these piscivorous fish in the China Seas increased during the early 1990s, stabilizing around 1.2 million tons after 1997. Principal component analysis (PCA) showed evident interannual-decadal variabilities in the catch of these fish with step changes around 1985/86 and 1997/98. Individual taxa, however, showed different trends in catches with sharks, rays, and lizardfishes manifesting downward trends while Pacific cod, eels, and hairtail increasing. Common dolphinfish and Japanese-Spanish mackerel increased largely in the 1990s but declined slightly during the 2000s. Although there were temporal overlaps between climate change and fishing variabilities, results of gradient forest analyses indicated that fishing effort imposed the most important influence on piscivorous fish. And among all climate variables explored in this study, sea surface temperature (SST) especially that of the East China Sea, had greatest impacts on variations in piscivorous fish catch, which may have been gradually exacerbated by the continued high fishing intensity. In addition, significant changes were identified in the life history traits in the species we evaluated, such as reduced average body sizes and truncated age compositions, strongly indicating the effect of fishing. We therefore advocate precautionary fishery practices under climate change.

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Safety of protease inhibitors and Arbidol for SARS-CoV-2 pneumonia in Zhejiang Province, China - Yong-zheng Guo; Kai-jin Xu; Yong-tao Li; Jia-dan Fu; Min Xu; Ling Yu; Ji-fang Sheng; Biao Zhu (Journal of Zhejiang University-SCIENCE B, 2020)

Whole-Brain Map of Long-Range Monosynaptic Inputs to Different Cell Types in the Amygdala of the Mouse - Jia-Yu Fu; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Meng-Yu Tang; Bin Yu; Xiao-Ming Li (Neuroscience Bulletin, 2020)
The amygdala, which is involved in various behaviors and emotions, is reported to connect with the whole brain. However, the long-range inputs of distinct cell types have not yet been defined. Here, we used a retrograde trans-synaptic rabies virus to generate a whole-brain map of inputs to the main cell types in the mouse amygdala. We identified 37 individual regions that projected to neurons expressing vesicular glutamate transporter 2, 78 regions to parvalbumin-expressing neurons, 104 regions to neurons expressing protein kinase C-δ, and 89 regions to somatostatin-expressing neurons. The amygdala received massive projections from the isocortex and striatum. Several nuclei, such as the caudate-putamen and the CA1 field of the hippocampus, exhibited input preferences to different cell types in the amygdala. Notably, we identified several novel input areas, including the substantia innominata and zona incerta. These findings provide anatomical evidence to help understand the precise connections and diverse functions of the amygdala.

The economic loss of health effect damages from PM2.5 pollution in the Central Plains Urban Agglomeration - Xiangshan Fu; Li Li; Yalin Lei; Sanmang Wu; Dan Yan; Ximing Luo; Hui Luo (Environmental Science and Pollution Research, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Nitrogen fertilizer enhances zinc and cadmium uptake by hyperaccumulator Sedum alfredii Hance - Ziwen Lin; Chunying Dou; Yongfu Li; Hailong Wang; Nabeel Khan Niazi; Shaobo Zhang; Dan Liu; Keli Zhao; Weijun Fu; Yongchun Li; Zhengqian Ye (Journal of Soils and Sediments, 2020)

Non-Gaussian Lagrangian Stochastic Model for Wind Field Simulation in the Surface Layer - Chao Liu; Li Fu; Dan Yang; David R. Miller; Junming Wang (Advances in Atmospheric Sciences, 2020)
Wind field simulation in the surface layer is often used to manage natural resources in terms of air quality, gene flow (through pollen drift), and plant disease transmission (spore dispersion). Although Lagrangian stochastic (LS) models describe stochastic wind behaviors, such models assume that wind velocities follow Gaussian distributions. However, measured surface-layer wind velocities show a strong skewness and kurtosis. This paper presents an improved model, a non-Gaussian LS model, which incorporates controllable non-Gaussian random variables to simulate the targeted non-Gaussian velocity distribution with more accurate skewness and kurtosis. Wind velocity statistics generated by the non-Gaussian model are evaluated by using the field data from the Cooperative Atmospheric Surface Exchange Study, October 1999 experimental dataset and comparing the data with statistics from the original Gaussian model. Results show that the non-Gaussian model improves the wind trajectory simulation by stably producing precise skewness and kurtosis in simulated wind velocities without sacrificing other features of the traditional Gaussian LS model, such as the accuracy in the mean and variance of simulated velocities. This improvement also leads to better accuracy in friction velocity (i.e., a coupling of three-dimensional velocities). The model can also accommodate various non-Gaussian wind fields and a wide range of skewness–kurtosis combinations. Moreover, improved skewness and kurtosis in the simulated velocity will result in a significantly different dispersion for wind/particle simulations. Thus, the non-Gaussian model is worth applying to wind field simulation in the surface layer.

Identification of rare variants in cardiac sodium channel β4-subunit gene SCN4B associated with ventricular tachycardia - Qin Yang; Hongbo Xiong; Chengqi Xu; Yuan Huang; Xin Tu; Gang Wu; Fenfen Fu; Zhijie Wang; Longfei Wang; Yuanyuan Zhao; Sisi Li; Yufeng Huang; et al. (Molecular Genetics and Genomics, 2019)

Effect of controlled-release fertilizer on N2O emissions and tea yield from a tea field in subtropical central China - Yanzheng Wu; Yong Li; Xiaoqing Fu; Jianlin Shen; Dan Chen; Yi Wang; Xinliang Liu; Runlin Xiao; Wenxue Wei; Jinshui Wu (Environmental Science and Pollution Research, 2018)

Conflicting meal recommendations for oral oncology drugs: pose risks to patient care? - Guo Yu; Dan-Na Wu; Yan Gong; Guo-Fu Li; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2018)

The variation of cloud amount and light rainy days under heavy pollution over South China during 1960–2009 - Chuanbo Fu; Li Dan (Environmental Science and Pollution Research, 2018)

Complexity measure of regional seasonal precipitation series based on wavelet entropy - Dong Liu; Qiang Fu; Dan Zhao; Tianxiao Li (Hydrological Sciences Journal, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Adhesion of bone marrow mesenchymal stem cells on porous titanium surfaces with strontium-doped hydroxyapatite coating - Dan-Li Fu; Qiao-hong Jiang; Fu-ming He; Bai-ping Fu (Journal of Zhejiang University-SCIENCE B, 2017)

Variations in forest aboveground biomass in Miyun Reservoir of Beijing over the past two decades - Li Fu; Dan Zhao; Bingfang Wu; Zhihong Xu; Yuan Zeng (Journal of Soils and Sediments, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Measurement and modeling of nitrous and nitric oxide emissions from a tea field in subtropical central China - Dan Chen; Yong Li; Cong Wang; Xiaoqing Fu; Xinliang Liu; Jianlin Shen; Yi Wang; Runlin Xiao; De Li Liu; Jinshui Wu (Nutrient Cycling in Agroecosystems, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Complexity measurement of regional groundwater resources system using improved Lempel-Ziv complexity algorithm - Dong Liu; Dan Zhao; Qiang Fu; Qiuchen Wu; Yongjia Zhang; Tianxiao Li; Khan M Imran; Faiz M Abrar (Arabian Journal of Geosciences, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Analysis of the Appropriate Development Scale of Regional Paddy Field Under the Restriction of Water Resources - Dong Liu; Dan Zhao; Qiang Fu; Tianxiao Li; Muhammad Imran Khan; Wenting Liu; Faiz M. Abrar (Agricultural Research, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Construction and pilot screening of a signature-tagged mutant library of Sinorhizobium fredii - Dan Wang; Yuan Chun Wang; Li Juan Wu; Jian Xin Liu; Pan Zhang; Jian Jiao; Hui Yan; Tao Liu; Chang Fu Tian; Wen Xin Chen (Archives of Microbiology, 2016)

Precipitation Complexity Measurement Using Multifractal Spectra Empirical Mode Decomposition Detrended Fluctuation Analysis - Dong Liu; Mingjie Luo; Qiang Fu; Yongjia Zhang; Khan M. Imran; Dan Zhao; Tianxiao Li; Faiz M. Abrar (Water Resources Management, 2016)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

An observational and modeling study of extratropical transition of Hurricane Sandy in 2012 - Dan Fu; Pengyuan Li; Gang Fu (Journal of Ocean University of China, 2015)

Performance of convective parameterization schemes in Asia using RegCM: Simulations in three typical regions for the period 1998–2002 - Shaukat Ali; Li Dan; Congbin Fu; Yang Yang (Advances in Atmospheric Sciences, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Trends in the different grades of precipitation over South China during 1960–2010 and the possible link with anthropogenic aerosols - Chuanbo Fu; Li Dan (Advances in Atmospheric Sciences, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

MicroRNA Expression Aberration in Chinese Patients with Relapsing Remitting Multiple Sclerosis - Dan Yang; Wei-Zhi Wang; Xue-Mei Zhang; Hui Yue; Bing Li; Lin Lin; Jin Fu (Journal of Molecular Neuroscience, 2014)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Comparison study between observation and simulation for sea fog over the Yellow Sea in May 2009 - Dan Fu; Shuai Wang; Delin Chen; Huaji Pang; Pengyuan Li (Journal of Ocean University of China, 2012)

Improved LASSO priors for shrinkage quantitative trait loci mapping - Ming Fang; Dan Jiang; Dandan Li; Runqing Yang; Weixuan Fu; Lijun Pu; Huijiang Gao; Guihua Wang; Liyun Yu (Theoretical and Applied Genetics, 2012)

Fluorescence microscopic analysis of bone osseointegration of strontium-substituted hydroxyapatite implants - Dan-li Fu; Qiao-hong Jiang; Fu-ming He; Guo-li Yang; Li Liu (Journal of Zhejiang University-SCIENCE B, 2012)

cDNA cloning and characterization of UDP-glucose: anthocyanidin 3-O-glucosyltransferase in Freesia hybrida - Xin Sui; Xiang Gao; Man Ao; Qinmei Wang; Dan Yang; Meng Wang; Yang Fu; Li Wang (Plant Cell Reports, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

Mycorrhizal synthesis of Tuber indicum with two indigenous hosts, Castanea mollissima and Pinus armandii - Li-Ying Geng; Xiang-Hua Wang; Fu-Qiang Yu; Xiao-Juan Deng; Xiao-Fei Tian; Xiao-Fei Shi; Xue-Dan Xie; Pei-Gui Liu; Yu-Ying Shen (Mycorrhiza, 2009)

Infection and replication of avian influenza H5N1 virus in an infected human - Jing-Jiao Zhou; Dan-Yun Fang; Jie Fu; Jiang Tian; Jun-Mei Zhou; Hui-Jun Yan; Yu Liang; Li-Fang Jiang (Virus Genes, 2009)